Politics of education and teachers' support for high-stakes teacher accountability policies - Oren Pizmony-Levy; Ashley Woolsey (Arizona State University, 2017)
Although educators are at the center of contentious high-stakes teacher accountability policies, we know very little about their attitudes toward these policies. This research gap is unfortunate because teachers are considered key actors in successful implementation of educational reforms. To what extent do the politics that accompany the introduction of high-stakes teacher accountability policies affect teachers' support for the policies themselves? To address this gap, we used data from an experimental survey of teachers in New Jersey (n=444), where a new reform-Teacher Effectiveness and Accountability for Children of New Jersey Act (TEACHNJ)-was signed into law in 2012 and implemented shortly after. The cornerstone of the reform is a new evaluation system that ties student performance on standardized tests to teachers' evaluation. We found that the majority of teachers oppose the new evaluation system. Teachers' attitudes were shaped by the politics of the key actors advocating for the policy, perceptions of implementation efforts, and beliefs in the potential outcome of the policy. Open-ended responses indicated that teachers question the validity of the evaluation system and are concerned about the negative intended and unintended consequences of the system. We conclude this paper by discussing the implications of these findings for policy studies and policymaking.